2014
DOI: 10.2147/opth.s56670
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent nontuberculous mycobacterial endophthalmitis: a diagnostic conundrum

Abstract: ObjectiveTo report a case of recurrent nontuberculous mycobacterial endophthalmitis in the context of neurotrophic keratopathy secondary to herpes zoster ophthalmicus that had an atypical presentation and complex course, and highlights the challenges of causative organism identification and therapeutic interventions in this condition.MethodsA retrospective chart review was conducted to determine the visual outcomes of the patient.ResultsA 68-year-old pseudophakic male with long-standing neurotrophic keratopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Clare and Mitchell reported a case of iris root abscess and necrotizing sclerokeratitis in an immunocompetent woman with no apparent risk factors [ 177 ]. Sclerokeratitis was seen after cataract surgery in 4 eyes [ 40 , 123 ], and keratitis leading to endophthalmitis was also seen in 6 eyes after cataract surgery [ 157 , 158 , 161 ] and 2 eyes after penetrating keratoplasty (PKP) [ 133 , 156 ]. In one case of an elderly lady with dry eyes, punctal plug insertion caused secondary upper lid canaliculitis and keratitis [ 29 ].…”
Section: General Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clare and Mitchell reported a case of iris root abscess and necrotizing sclerokeratitis in an immunocompetent woman with no apparent risk factors [ 177 ]. Sclerokeratitis was seen after cataract surgery in 4 eyes [ 40 , 123 ], and keratitis leading to endophthalmitis was also seen in 6 eyes after cataract surgery [ 157 , 158 , 161 ] and 2 eyes after penetrating keratoplasty (PKP) [ 133 , 156 ]. In one case of an elderly lady with dry eyes, punctal plug insertion caused secondary upper lid canaliculitis and keratitis [ 29 ].…”
Section: General Resultsmentioning
confidence: 99%
“…Isolates grown on culture media can be speciated by genotypic and molecular techniques as they allow for a rapid identification of NTM. In our review it is evident that there is increasing utilization of PCR and PCR probes/hybridization to accurately and rapidly identify specific NTM species [ 54 , 61 , 87 , 121 , 130 , 144 , 145 , 151 , 154 156 , 178 ]. Another genotypic method that was frequently employed is the PCR restriction endonuclease analysis [ 35 , 45 , 165 ].…”
Section: Discussionmentioning
confidence: 99%
“…This presentation led to early vitrectomy resulting in a successful treatment. From literature review, there were only 11 eyes that showed final BCVA of 6/60 or better [ 7 , 21 , 30 , 32 , 37 , 41 , 43 , 47 , 52 ]. Stewart et al reported a case of M. abscessus endophthalmitis with a full visual recovery [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional searches in PROQOLID and clincialtrials.gov were conducted to identify PROs used in NK or other eye disease clinical trial programs. Symptoms and signs reported in the literature review related to NK included: redness, discomfort, inflammation, decreased corneal sensation, dryness, decreased tear production, reduced visual acuity, and irregular blinking (if bilateral disease) [1,3,19,20]; however, some patients are asymptomatic [8,19]. Although several existing PROs for eye disease were identified, [21][22][23][24][25][26] a gap analysis of each tool's content showed that none of them adequately assessed the symptoms, signs, and impacts of patients with NK.…”
Section: Introductionmentioning
confidence: 99%